Développer la recherche d’information et l’autorégulation collective en classe renversée : l’apport des tests d’autoévaluation - Laetitia Thobois Jacob; Emmanuelle Chevry Pébayle (Revue Internationale de Pédagogie de l’Enseignement Supérieur, 2020)
enA kind of flipped class, literally called « reversed classroom » (Cailliez et Hénin, 2017) is a promising instructional design which focusses on creativity and « hands on » activities. However, we know little about the learning gains that might occur in this environment. In our view, these gains are unlikely to happen unless some help is provided to manage the high cognitive load and support students’ self-regulated learning. Roediger et Karpicke (2006) suggest that self-assessments support cognitive and metacognitive learning strategies. Could they help students develop a socially constructed self-regulated learning?This paper presents an experiment that took place in a Digital Culture course of DUT Information-Communication with first-year students, in order to sensitize students to digital literacy and to develop their informational literacy skills. Another issue is the social challenges that students have to face as this class expects them to work in collaborative learning groups : in this context, students will have to regulate their motivation together and achieve socially constructed self-regulated learning (Cosnefroy et Jézégou, 2013; Järvela et Järvenoja, 2011). Two types of self-assessment tests were implemented : classical multiple-choice tests and free-recall tests. Our results show that correlations occur between multiple-choice tests and learning gains whereas free-recall tests are correlated to performance. Also, these free-recall tests indirectly lead to collective self-regulatory learning strategies among students.